International development institutions and the challenges of urbanisation: the case of Jakarta. Issue 3 (2nd April 2016) - Essex, Jamey
ABSTRACT: Urbanisation in the Global South presents numerous challenges for international development institutions. Building from interviews at nine different international development institutions working in Jakarta, Indonesia, this article examines how such institutions approach urban poverty, governance, and collaboration. The case study of Jakarta indicates that urban governance is often fragmented and difficult for such institutions to navigate, making partnership with other, often local, actors and institutions with urban and on-the-ground expertise vital. International development institutions struggle to both address the unique characteristics of distinct urban areas and to develop widely replicable practices, strategies, and platforms for effective partnership and development intervention.